Optimizing New Habits In New Normal Era Through Community Service In Paninggilan - Intan Tri Utami; Shabrina Talitha Andani; Wahyunengsih Wahyunengsih (PROMOTOR, 2023)
Before the arrival of the New Normal era, Indonesia had been in the highest position, namely, as the country with the most cases, it holds the 13th position globally, Covid-19 cases with a total of 4,174,216 cases. The arrival of the New Normal era is good news for Indonesia as a sign of Indonesia's success in reducing Covid-19 cases. Therefore, the optimization of Covid-19 in this new normal era aims to overcome Covid-19 cases by optimizing new habits through community service. Optimization of new habits with the corona virus, namely that people begin to adapt to face the pandemic and carry out a new normal life with the requirements to follow health protocols while doing activities outside the home. The goal of this study is to improve the public understanding, knowledge, and awareness to always apply health protocols and create a healthy Paninggilan area through community service. This research uses a qualitative research methodology. This research was conducted through interview process with the Head of Paninggilan Neighbourhood. According to the result of this research, Paninggilan residents understand and comply with health protocols with new healthy habits that have been applied in their daily lives.